1997
DOI: 10.1177/002194369703400306
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Genre of a Business Fax: A Finnish Case Study

Abstract: The faxes sent and received during one week by a small Finnish company involved in international operations were analyzed to determine whether or not the business fax contains distinct features that warrant classifying it as a genre. Using a framework of critical discourse analysis, the study looked at a total of 69 faxes. The results suggest that the business fax is a distinct, dynamic genre that is constituted by and constitutive of the social practices within which it is situated. Five specific subgenres of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 5 publications
3
19
0
Order By: Relevance
“…This notion of one email genre entailed that the messages were viewed on a high level of abstraction or generality and that they would be comparable to the genre of the business fax or to that of the business letter (see Yates & Orlikowski 1992, Louhiala-Salminen 1997. As the present analysis was more detailed, it also revealed differences in the distribution of the framing moves (e.g.…”
Section: Summary -Support For Three Email Genresmentioning
confidence: 74%
See 2 more Smart Citations
“…This notion of one email genre entailed that the messages were viewed on a high level of abstraction or generality and that they would be comparable to the genre of the business fax or to that of the business letter (see Yates & Orlikowski 1992, Louhiala-Salminen 1997. As the present analysis was more detailed, it also revealed differences in the distribution of the framing moves (e.g.…”
Section: Summary -Support For Three Email Genresmentioning
confidence: 74%
“…In today's world, and especially in international business, communication for business purposes is increasingly carried on via email messages, the share of faxes is decreasing, and business letters are rare (see also . Louhiala-Salminen (1997 further suggests that the medium does not leave the message untouched; when the writer decides to write a fax and starts to write it on a fax form, he/she will be aware of the generic constraints and the unmarked conventions that the recipient expects him/her to follow. Drawing on this, it can be suggested that when the writer faces an email template on the computer screen, the generic constraints to be followed will be different than if he/she faced a letter template in Microsoft Word.…”
Section: Form Of Genresmentioning
confidence: 99%
See 1 more Smart Citation
“…3. I am aware of the discussion of stressing faxes as a genre (Louhiala-Salminen, 1997). However, these are not part of the concern of this paper which looks at text as part of written discourse but views it from the genre perspective.…”
Section: University Of Queenslandmentioning
confidence: 98%
“…First of all, genre is characterised by its purpose, form and content (Olikowski and Yates 1994), which are also the first type of genre knowledge and are often used as criteria for identifying business and professional genres such as faxes and emails (Louhiala-Salminen 1997;Gimenez 2004). These features are also seen as fundamental components of genre knowledge.…”
Section: Genre Knowledge and Discursive Competence Across Culturesmentioning
confidence: 99%